Does Bid/Ask Spread React to the Increase of Internet Search Traffic? - Nurazi, Ridwan; Usman, Berto; Kananlua, Paulus S. (Universitas Prasetiya Mulya, 2015)
This article solely examines the effect of investor attentions on bid-ask spread. We find that investors’ attention surrogated by Internet Search Traffic (IST) contribute positively and significantly toward bid-ask spread (SPREAD). This result indicates that the incoming information directs the market within the stack circumstance and thin trading activity. Here, our samples were obtained from the manufacturing index, in the Indonesia Stock Exchange (IDX) during the period of observation ranging from 2009 to 2011. The hypothesis testing in this research is performed by using panel data regression analysis (Fixed Effect Model). Test result reveals that the search of online information through Google is beneficially one of the efforts to reduce asymmetry information between informed investors and uninformed investors. Besides, we also note that asymmetric information not only exists between the informed and uninformed investors, but also happens to market makers and informed investors. Finally, our findings lead to a conclusion, in which the high search of information tends to help investors in making appropriate investment decisions.